Development of Under-five Wasting Children and Related Factors in Padang City - Desmawati Desmawati; Febri Theresia Sihaloho; Bobby Indra Utama (Amerta Nutrition)
Background: At the age of under five years, there is rapid physical, cognitive, social, and emotional development, which influences their future abilities. The prevalence of wasting in Indonesia is 7.7%, but it has not received serious attention, so it needs to be explored further.